(untitled) (Modern education and development, 2024)
Vitamin C is essential for the development and proper functioning of the body. Ascorbic acid plays an important role in the immune system. It is often recommended to get vitamin C from the diet rather than taking supplements. Fresh oranges and freshly squeezed orange juice are good sources of vitamin C. Fresh fruits and vegetables, especially citrus fruits, are also important sources of vitamins. But today, as a result of various biochemical studies, it has become clear that peaches contain relatively more vitamin C. Not only its fruits, but also its leaves have been studied for vitamin C content, and its use as a medicinal raw material is currently considered relevant.